(untitled) (Baghdad Science Journal, 2008)
Two kinds of alternative media (domestic wastewater and inorganic fertilizers) were used for cultivation of diatom Nitzschiapalea (Kuetz.)W. Smith in control conditions (temperature 25°C and light intensity 260 µE/m²/sec). These media were mixed with modified Chu-10 medium. Highest growth rate (0.56 cell/h) and lowest doubling time (13 cell/h) recorded for 50% wastewater supported with Chu-10. Followed, by inorganic fertilizers media formed of 125mg/L N:P:K, 12.5mg/L supper phosphate P2O5, 100 mg/L magnesium sulphate and 10 mg/L sodium silicate, which gives 0.35 cell/h of growth rate, 20.75 h doubling time, 9.75 × 106 cell/ml of cells count and absorption of 0.86 nm. So, its enable to benefit from wastewater and inorganic fertilizers as alternative media for cultivation this algal species and it is easy to obtain for reducing the cost of production.